Analisis Pengaruh Harga Dan Brand Trust Terhadap Brand Loyality Kosmetik Wardah - mawardi mawardi; Imi Martalia Giti (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
The purpose of the study was to partially examine the effect of Price on Wardah Cosmetics Brand Loyalty at BhontodBeauty Stores, to test the effect of Brand Trust on Wardah Cosmetics Brand Loyalty at BhontodBeauty Stores in simulant and the most dominant variable influencing Wardah Cosmetics Brand Loyalty at BhontodBeauty Stores. The results of the calculation of the F test show that the F value is 22.864 while the F table value is 2.77, this means that F count> F table, so it can be concluded that the variable price and brand trust simultaneously / jointly affect brand loyalty. The t value of brand trust generated is 4.665, while the t table value is 1.672, this means that t> t table, meaning that the brand trust variables individually always show their effect on brand loyalty. For the variable price the value of t generated is 0.739, while the value of t table is 1.672, this means that t count <t table, meaning that the price variable by itself has no effect on brand loyalty. The number R is 0.667, this means that the correlation or relationship between price and brand trust with brand loyalty is Strong / Large, because the number 66.7% is above 50% and close to 100%. The adjusted R square number (percentage correlation) is 0.426, this means that 42.6% of brand loyalty can be explained or influenced by price and brand trust variables, while the remaining 57.4% is influenced by other causes not included in this study. Keywords: Price, Brand Trust, Brand Loyalty.